PEMIKIRAN FATIMA MERNISSI TENTANG PENDIDIKAN ISLAM PERSPEKTIF GENDER - Siti Yumnah Syaukani (Ta`Limuna: Jurnal Pendidikan Islam, 2021)
Abstract : In the current era of globalization, gender studies are no longer unfamiliar, given that so many discourses will develop in the mainstream of gender in all aspects of life, especially education. Education which is a strategic tool in making changes, especially Islamic education is expected to be able to answer this challenge, where there is a discourse that Islam is a religion that upholds patriarchal culture, which raises female activists in Islam, one of which is Fatima Mernissi, which seeks to interpret the existence of bias gender in the scriptures. by borrowing the enthusiasm of Fatima Mernissi in interpreting patriarchal biased verses which state that it is not religion that causes problems but rather in its interpretation it is hoped that Islamic education will be able to be more wise in viewing holy verses that are gender biased and continue to strive to do a review in order to realize them. Islamic education in accordance with its objectives.Keyword : Fatima Mernissi, Islamic Education, Gender